Taxonomic revision and phylogeny of the ant genus Prenolepis (Hymenoptera: Formicidae) - Williams, Jason L.; Lapolla, John S. (Zootaxa, 2016)
The formicine ant genus Prenolepis is here revised for the first time. Thirteen extant species are recognized of which four are described as new. A key for the worker caste is provided, and the worker of each species is imaged, with males and queens imaged in species where they are known. Worker-based characters were used to construct a species-level phylogeny of Prenolepis. Both maximum parsimony and Bayesian inference methods were used for the phylogenetic analyses. A morphological diagnosis for the genus is provided, with a discussion of useful morphological characters for separating Prenolepis from other genera in the Prenolepis genus-group. Major taxonomic changes are proposed. The new species are: P. darlena, P. fustinoda, P. mediops, and P. shanialena. Prenolepis jerdoni subopaca is elevated to full species. Three species are excluded from Prenolepis and transferred to Nylanderia and Paratrechina as new combinations: N. emmae, N. flaviabdominis, and P. umbra. Two species are excluded from Paratrechina and transferred to Nylanderia and Paraparatrechina as new combinations: N. guanyin and P. kongming. One species, Z. darlingtoni, is excluded from Nylanderia and transferred to Zatania as a new combination. Several synonyms are proposed: Prenolepis sphingthoraxa = Nylanderia flaviabdominis; P. imparis arizonica, P. imparis colimana, P. imparis coloradensis, and P. imparis veracruzensis = P. imparis; P. melanogaster carinifrons and P. nigriflagella = P. melanogaster; P. longiventris and P. magnocula = P. naoroji; and P. septemdenta = Nylanderia opisopthalmia.